The guns of August - Tuchman, Barbara W. (Barbara Wertheim) 1912-1989 (The Random House Publishing Group, 1994)
"More dramatic than fiction ... THE GUNS OF AUGUST is a magnificent narrative--beautifully organized, elegantly phrased, skillfully paced and sustained ... The product of painstaking and sophisticated research." CHICAGO TRIBUNE Historian and Pulitzer Prize-winning author Barbara Tuchman has brought to life again the people and events that led up to World War I. With attention to fascinating detail, and an intense knowledge of her subject and its characters, Ms. Tuchman reveals, for the first time, just how the war started, why, and why it could have been stopped but wasn't. A classic historical survey of a time and a people we all need to know more about, THE GUNS OF AUGUST will not be forgotten.